For the poor or the poorest? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Florence Chiburesha explaining how the Women Finance Co-operative is supporting development for Zambian women and their families.